2007
DOI: 10.1042/bj20070664
|View full text |Cite
|
Sign up to set email alerts
|

Secreted PCSK9 promotes LDL receptor degradation independently of proteolytic activity

Abstract: PCSK9 (proprotein convertase subtilisin/kexin 9) is a secreted serine protease that regulates cholesterol homoeostasis by inducing post-translational degradation of hepatic LDL-R [LDL (low-density lipoprotein) receptor]. Intramolecular autocatalytic processing of the PCSK9 zymogen in the endoplasmic reticulum results in a tightly associated complex between the prodomain and the catalytic domain. Although the autocatalytic processing event is required for proper secretion of PCSK9, the requirement of proteolyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(92 citation statements)
references
References 24 publications
5
87
0
Order By: Relevance
“…Elegant studies have shown previously that coexpressed PD trans-acts on PD-deficient PCSK9 and enables the latter to be secreted (27,28). We clearly confirmed these results in this study.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Elegant studies have shown previously that coexpressed PD trans-acts on PD-deficient PCSK9 and enables the latter to be secreted (27,28). We clearly confirmed these results in this study.…”
Section: Discussionsupporting
confidence: 82%
“…Fig. 2A shows that deletion of the entire PD protein abolished both the secretion and LDLR-reducing activity of PCSK9, consistent with previous reports (27,28). Separate deletions of PD residues 31-40, 41-50, and 51-60 did not significantly affect PCSK9 processing, secretion, or function, except for a modest effect of ⌬51-60 on autoprocessing.…”
Section: Secretion and Function Of Pcsk9 Truncation Mutants-wesupporting
confidence: 80%
See 2 more Smart Citations
“…Thus, PCSK9 functions as a chaperone to prevent LDL receptor recycling and/or target LDL receptors for lysosomal degradation. Furthermore, the ability of PCSK9 to degrade the LDL receptor is independent of its catalytic activity [McNutt et al, 2007;Li et al, 2007]. The role of PCSK9 serine protease activity seems limited to catalyzing the selfcleavage of pro-PCSK9, which is essential for PCSK9 secretion from liver cells and for the reduction of the number of LDL receptors [Zhang et al, 2007].…”
Section: Impact Of Pcsk9 On the Ldl Receptormentioning
confidence: 99%